THE PECULIARITIES OF THE METHODS OF TEACHING CONDUCTOR SCIENCE - Omarova Anarxan Kislaubayevna (Galaxy International Interdisciplinary Research Journal, 2021)
Conductor art has a long and ancient history. Since people began to sing together, the need to adhere to the general rhythm and pace appeared in them. In the dance and songs of the primitive people, those who gave the rhythm an applause, as well as those who beat with a bang or a drum click. In ancient Greece, there were xor leaders, who beat their legs and set a rhythm. Even more so, it is known that in the Roman singing school used certain hand movements to manage. These two methods of conduction were based on orchestral management, the conductor beat the tact with his foot, knocking the remote control or floor with a stick, and again also stroking the remote control with a note pad wrapped around. In this article, opinions and comments are made about the peculiarities of the methods of teaching conductor Science in modern society.